The Worst-First Heuristic: How Decision Makers Manage Conjunctive Risk - Lewis, Joshua; Feiler, Daniel; Adner, Ron (Management Science, 2023)
Many important managerial outcomes hinge on the co-occurrence of multiple uncertain events, a situation termed conjunctive risk. Whereas past literature has addressed the psychology of choosing to enter situations with conjunctive risk, this article elucidates a novel way in which the psychology of managing conjunctive risk is importantly distinct. We examine a case in which there are two independent events, one is currently less likely than the other, both are required for overall success, and the decision maker must evaluate opportunities to increase the chance of the less-likely or more-likely requirement. We introduce the hypothesis of a worst-first heuristic. Decision makers intuitively evaluate improvements in conjunctive risk according to their impact on the biggest barrier to success, the least likely of the required events. We find evidence for such a worst-first heuristic across nine experiments (n = 3,653, including samples from the United States and United Kingdom in Studies 1–5 and Studies S1–S3 in the online supplement, as well as a sample of managers in Study 6). Participants invest more to improve chances of less-likely requirements than more-likely requirements, even when the latter improvements have at least as much impact on the aggregate chance of success. Moreover, we find that decision makers exhibit this behavior particularly when managing conjunctive risk, as doing so makes them attend to which threat is the worst. Conversely, they do not appear to exhibit the behavior when making formally equivalent decisions about choosing between conjunctive risks. This bias toward underinvesting in stronger-links holds important implications for decision making in contexts subject to conjunctive risk—both managerial and societal. This paper was accepted by Yuval Rottenstreich, behavioral economics and decision analysis. Supplemental Material: Data and the e-companion are available at https://doi.org/10.1287/mnsc.2022.4411 .